Dual-fuel MK KY burner fired with agropellet - Pilarski, Sławomir; Martychowiec, Sylwia (Instal, 2021)
The design and principles of operation of the innovative MK KY dual-fuel burner, which operates with inferior in quality agropellet as fuel are presented in this article. A diagram of the burner’s construction, the authorial algorithm of the burner’s operating and self-cleaning procedures as well as features and advantages of the MK KY dual-burner over commercial burners are discussed.